2007
DOI: 10.1177/0145445506295055
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Intervention Strategies to Alleviate Preoperative Anxiety in Children

Abstract: Preoperative anxiety (anxiety regarding impending surgical experience) in children is a common phenomenon that has been associated with a number of negative behaviors during the surgery experience (e.g., agitation, crying, spontaneous urination, and the need for physical restraint during anesthetic induction). Preoperative anxiety has also been associated with the display of a number of maladaptive behaviors postsurgery, including postoperative pain, sleeping disturbances, parent-child conflict, and separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(155 citation statements)
references
References 102 publications
(97 reference statements)
3
145
0
7
Order By: Relevance
“…2,3 Benzodiazepines are firstline treatments for patients who exhibit clinically significant preoperative anxiety. 4,5 Although novel anti-anxiety techniques/agents continue to be investigated for the pediatric population, 6,7 there have been very few studies examining novel pharmacological interventions for the treatment of preoperative anxiety in adults. Recent studies have investigated the efficacy of the a2d (alpha-2-delta) voltage-dependent calcium channel blockers (gabapentin and pregabalin) for the treatment of preoperative anxiety, and there have been mixed results regarding the efficacy of gabapentin.…”
Section: Résumémentioning
confidence: 99%
“…2,3 Benzodiazepines are firstline treatments for patients who exhibit clinically significant preoperative anxiety. 4,5 Although novel anti-anxiety techniques/agents continue to be investigated for the pediatric population, 6,7 there have been very few studies examining novel pharmacological interventions for the treatment of preoperative anxiety in adults. Recent studies have investigated the efficacy of the a2d (alpha-2-delta) voltage-dependent calcium channel blockers (gabapentin and pregabalin) for the treatment of preoperative anxiety, and there have been mixed results regarding the efficacy of gabapentin.…”
Section: Résumémentioning
confidence: 99%
“…An increase in parental anxiety has been shown to be positively related with their child's anxiety levels and fears during medical procedures (e.g. Kain et al, 2003;Wright et al, 2007), which may be a consequence of a contagious interaction (Jay, Ozolins, Elliott & Caldwell, 1983). Several studies have documented this relationship between child and parental anxiety (Fincher, Shaw & Ramelet, 2012).…”
mentioning
confidence: 99%
“…The majority of the studies comprise the ones related to anesthesia and surgical interventions. It has been determined that more than 40-60% of the children undergo anxiety and fear in the preoperative period, especially during anesthesia induction [14,16,17]. Wollins et al have shown that hospital setting causes anxiety in approximately 38% of the children between the ages of 5-12 undergoing elective surgery and again that a high degree of anxiety is observed in the preoperative period in 53% of these children [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Both pharmacologic (like sedatives) and non-pharmacologic (presence of family, behavioral preparation programs, music, acupuncture, and etc) approaches have been proven to be useful [17]. Özen at al.…”
Section: Discussionmentioning
confidence: 99%